Synthesis and Characterization of the Manganese Hydroxide Halides Mn(OH)X (X = Br, I) and Crystal Structure of trans‐MnBr2·4H2O. Issue 14 (4th July 2019) - Falkowski, Viktoria; Zeugner, Alexander; Isaeva, Anna; Wurst, Klaus; Ruck, Michael; Huppertz, Hubert
Abstract : The pale‐pink, hygroscopic compounds Mn(OH) X ( X = Br, I) were obtained by high‐pressure synthesis in a Walker‐type multianvil apparatus. They crystallize in the space group P 21 / c with a = 640.48(3), b = 698.80(3), c = 615.54(2) pm, β = 110.30(1)° at 183(1) K ( X = Br), and a = 686.18(3), b = 713.08(3), c = 637.18(3) pm, β = 109.51(1)° at 150(1) K ( X = I). The crystal structures are isotypic to Cu(OH)Cl and consist of edge‐sharing distorted Mn(OH)3 X 3 octahedra arranged in sheets parallel to the bc ‐plane. Spin‐polarized scalar‐relativistic DFT+ U calculations predict an intrinsic magnetic insulating state (ca. 3.5 eV bandgap) that is proximate to frustration. Calculated effective magnetic moments equal to 4.34 μB /f.u. for Mn(OH)Br and 4.33 μB /f.u. for Mn(OH)I. FT‐IR spectroscopy confirmed interlayer hydrogen bonding. As a side result of the experiments, the compound trans ‐MnBr2 · 4H2 O was obtained. It crystallizes in the space group Cmcm with a = 438.64(2), b = 1167.84(6), and c = 730.95(4) pm. Abstract :